Importance of proper drying and storage in maintaining the quality of pepper seeds (Capsicum) (Research, Society and Development, 2023)
Despite appearing to be of little importance to agriculture, the chili pepper (Capsicum) production sector is very extensive and promising, forming a fundamental part of Brazilian agribusiness. The aim of this study was to carry out a narrative review of the main factors relating to the use of different drying methods and storage temperatures for chili seeds, and how they affect the maintenance of physiological quality. As for the methodology, the study model was based on exploratory bibliographical research and a qualitative approach, providing information on appropriate drying and storage for maintaining the quality of pepper seeds, addressing the aspects and factors that directly interfere in these processes. The literature consulted showed that drying and storage have a direct influence on seed quality, but it is important to point out that processes in the field, such as the right time to harvest, also have a significant impact. As the sector is developing, there is a significant need for research into seed production technology with high genetic, physical, physiological and health quality, resulting in greater final productivity, with drying and storage being crucial stages in this process. Through the findings, it was possible to see how important it is to carry out adequate drying and storage to maintain vigor, using specific temperatures and conditions as required for pepper seeds. Although there are a large number of publications on the management and production of chili peppers, there is a need for more specific studies that identify the optimization of the seed production process, as well as drying and storage operations.